Sulforaphane protects intestinal epithelial cells against lipopolysaccharide-induced injury by activating the AMPK/SIRT1/PGC-1ɑ pathway. Issue 1 (1st January 2021) - Zhang, Yu-jie; Wu, Qian
ABSTRACT: The naturally occurring isothiocyanate sulforaphane, found in vegetables, shows promising anti-inflammatory, anti-apoptosis, and anti-oxidative effects. Whether sulforaphane protects against lipopolysaccharide (LPS)-induced injury in intestinal epithelial cells is unclear. The present study examines the ability of sulforaphane to protect Caco-2 cultures from LPS-induced injury, as well as the mechanism involved. Caco-2 cells were incubated for 24 h with 1 μg/mL LPS and different concentrations of sulforaphane (0.1–10 μM). Then, various indicators of oxidative stress, inflammation, apoptosis, and intestinal permeability were assayed. Sulforaphane increased cell viability and reduced lactate dehydrogenase activity in LPS-treated Caco-2 cells in a concentration-dependent manner. Sulforaphane weakened LPS-induced increases in intestinal epithelial cell permeability and oxidative stress (based on assays of reactive oxygen species, DMA, and H2 O2 ), and it increased levels of antioxidants (SOD, GPx, CAT and T-AOC). At the same time, sulforaphane weakened the ability of LPS to induce production of inflammatory cytokines (IL-1β, IL-6, IL-8 and TNF-α) and the pro-apoptotic caspases-3 and −9. Sulforaphane also upregulated p-AMPK, SIRT1, and PGC-1ɑ, whose inhibitors antagonized the compound's protective effects. Sulforaphane can protect intestinal epithelial cells against LPS-induced changes in intestinal permeability, oxidative stress, inflammation, and apoptosis. It appears to act by activating the AMPK/SIRT1/PGC-1ɑ pathway. The drug therefore shows potential for preventing LPS-induced intestinal injury. GRAPHICAL ABSTRACT: uf0001